Curing efficacy of light emitting diodes of dental curing units - Seyd Mostafa Mousavinasab; Ian Meyers (Tabriz University of Medical Sciences, 2009)
Background and aims. The aim of the present study was to compare the efficacy of quartz tungsten halogen (QTH) and light emitting diode (LED) curing lights on polymerization of resin composite.
Materials and Methods. A hybrid resin composite was used to prepare samples which were cured using two QTH and ten LED light curing sources. Twelve groups, each containing ten samples, were prepared using each light source. The cured depth of the resin was determined using ISO 4049 method and Vickers hardness values were determined at 1.0 mm intervals. Data was analyzed by ANOVA and Tukey test.
Results. Data analysis demonstrated a significant difference between light sources for depth of cure. At 1.0 mm below the surface all the tested light sources and at 2.0-mm intervals all light sources except two (Optilux 501 and LEDemetron I) and at 3.0-mm intervals only two light sources (PenCure and LEDemetron II) could produce hardness values higher than 80% of superficial layer values.
Conclusion. This study showed that a variety of LED light sources used in the present study are as effective as the high-intensity QTH lights in polymerization of resin composite.